#TITLE_ALTERNATIVE# - ADI PERMANA , GUMBIRA
Rock compaction may occur in producing petroleum reservoirs. The weight of overburden sediments above a producing formation is supported partially by the rock matrix and partially by the pressurized fluid within the rock pore space. When the fluid pressure is reduced, more of the load is transferred to the rock matrix, and the formation is compacted. Rock compaction causes problems in multiple scales. For instance, compaction can reduce formation porosity and permeability, affecting long-term hydrocarbon production from the reservoir. Compaction can also deform well tubular, creating operational problems and shortening well lives. If compaction is significant, it can cause subsidence of the ocean floor, leading to severe safety problems for offshore platforms. Subsidence in X Field was caused by reservoir compaction as a result of pore-pressure decline during hydrocarbon production period. In general, reservoir pressure depends on the depth hydrocarbon accumulation. The weight of the overlying sediments is transmitted to the fluid and grain structure in the reservoir. As hydrocarbons are produced, the fluid pressure will decline and the load of the formation rock will increase. The increased load on the formation rock causes the reservoir to compact. Total compaction of the reservoir is therefore related to the decrease in formation pressure, physical properties of rock, and the thickness of the formation.